Monitoring & Evaluasi Sebagai Konsensus Untuk Mencapai Efektivitas Pemanfaatan Pinjaman/Hibah Luar Negeri - Umi Hanik; Heru Subiyantoro (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2010)
Wangwe (1997) on his study "The Management of Foreign Aid in Tanzania‟ noted that the weaknesses of monitoring and accountability mechanism resulted to a failure of the fulfillment of aid commitments utilization; it also caused a decline in the trust of the donors and the decrease of government credibility over donors. Furthermore, several studies and the results of the auditor agency (BPK) found that the ineffectiveness of the implementation of M&E resulted to the lack of performance of the development aid. We apply a descriptive analysis to capture the relation of M&E and aid effectiveness in Indonesia. Answering Wangwe (1997) and the findings tell us the cosistencies with that of Paris Declaration as an international concencus on aid effectiveness existed to optimize the M&E function as well as to achieve its five principles: 1) Ownership; 2) Harmonization; 3) Alignment; 4) Results; and 5) mutual accountability for aid effectiveness. Analyzing the implementation in Indonesia, we should appreciate the Government of Indonesia who has achieved in gathering 22 bilateral and multilateral donors institutions to sign a commitment for aid effectiveness in Indonesia. Jakarta's commitment brings to a new paradigm on how foreign aid will be well managed.